Generator stator windings ground fault diagnosis for generator–grid​ directly connected system of floating nuclear power plant - Yikai Wang (Elsevier, 2021)
For floating nuclear power plants, the internal power system adopts the generator–grid directly connected structure. Generator ground fault diagnosis enables the protective device to adaptively determine the generator tripping control mode based on the fault degree, and shorten the troubleshooting time by fault location. To accurately calculate the ground fault current under different system operating modes, a real-time grounding capacitance parameters calculation method without injection devices is proposed based on third harmonic voltage. Using the fault component principle, the ground fault current is calculated including the fundamental and the third harmonic components. Through fuzzy membership function, the ground fault degree function is established including the ground fault current and the system overvoltage. It comprehensively reflects the damage degree of both the generator operating security and the system insulation security. According to the 60° phase-band distribution characteristic of the stator windings, a fault coil location method based on the windings’ electric potential distribution characteristics is proposed. PSCAD/EMTDC simulation results show that the proposed method has high computational accuracy.